2021
DOI: 10.1186/s13567-020-00886-7
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid protein 2 of Eimeria maxima provided partial protection against infection by homologous species

Abstract: Rhomboid-like proteases (ROMs) are considered as new candidate antigens for developing new-generation vaccines due to their important role involved in the invasion of apicomplexan protozoa. In prior works, we obtained a ROM2 sequence of Eimeria maxima (EmROM2). This study was conducted to evaluate the immunogenicity and protective efficacy of EmROM2 recombinant protein (rEmROM2) and EmROM2 DNA (pVAX1-EmROM2) against infection by Eimeria maxima (E. maxima). Firstly, Western blot assay was conducted to analyze t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
1
0
0
Order By: Relevance
“…In Cryptosporidium baileyi, Yang et al reported that vaccination with a DNA vaccine of pEGFP-CbROM reduced fecal oocyst burden (71.3%) in chickens after infection by C. baileyi (43). In Eimeria, ROMs have been reported to provide partial protection against homologous infection in the form of DNA vaccine, recombinant subunit vaccine, or recombinant BCG vaccine (22,39,(43)(44)(45)(46)(47). These studies are consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…In Cryptosporidium baileyi, Yang et al reported that vaccination with a DNA vaccine of pEGFP-CbROM reduced fecal oocyst burden (71.3%) in chickens after infection by C. baileyi (43). In Eimeria, ROMs have been reported to provide partial protection against homologous infection in the form of DNA vaccine, recombinant subunit vaccine, or recombinant BCG vaccine (22,39,(43)(44)(45)(46)(47). These studies are consistent with our findings.…”
Section: Discussionsupporting
confidence: 91%